Randomised trial comparing assist control and pressure support ventilation during weaning. (4th April 2011) - Shefali-Patel, D; Hannam, S; Lee, S; Rafferty, G; Greenough, A
Abstract : Aim: Assist control ventilation (ACV) compared to pressure limited, time cycled ventilation is associated with shorter duration of weaning. During both ACV and pressure support ventilation (PSV), all the infant's breaths are supported by positive pressure inflations but, during PSV, both the timing of the start and end of inflation are determined by the infant's respiratory efforts and hence asynchrony may be less likely. Inflation times, however, can be short during PSV and this may increase the work of breathing and adversely affect respiratory muscle strength. The aims of this study, therefore, were to determine whether the duration of weaning differed between infants weaned by PSV or ACV and if any differences related to the differences in the work of breathing, asynchrony or respiratory muscle strength. Methods: 36 infants, median gestational age 30 (range 21–39) weeks, were randomised to weaning by either ACV or PSV. The duration of weaning was recorded. At baseline (study entry), 24 h after entering the study and immediately prior to extubation using the transdiaphragmatic pressure time product (PTPdi), an assessment of the work of breathing, was measured. A dual tipped pressure transducer was used to measure oesophageal and gastric pressures and the transdiaphragmatic pressure calculated by digital subtraction of the oesophageal from the gastric pressure. PTPdi was calculated by integration of the transdiaphragmatic pressure signal with time for each breath and expressed per minute. The mean PTPdi was calculated from 20 consecutive breaths. In addition, asynchrony (TAA) was assessed using respiratory inductance plethysmography and respiratory muscle strength measured by recording the maximal inspiratory pressure produced during a maintained airway occlusion during crying (Pimax). Results: The median duration of weaning was 33.7 (range 7–100) h in the ACV group and 26.7 (range 9.75–168.8) h in the PSV group (p=0.88). There were no significant differences in the median PTPdi, TAA or Pimax results between the two groups. Conclusion: Weaning modes which support all of the infant's breaths are equally efficacious.